When social practices produce space and create passive cooling systems in hot arid region - Benoudjafer, Ibtissame (Technium Social Sciences Journal, 2022)
Abstract. Practice social of people is the key to produce space and give a possibility to maintain thermal comfort and energy efficiency. The main objective of this research is to adapt the traditional strategies in the architecture actual, to achieved a thermal comfort and improve on reducing cooling load through the using of vernacular gait. Today, it is necessary to practice these systems in the current or conventional architecture of household. The study is especially for arid cities namely the region of Saoura, in the hot and dry climatic zone in Algeria, considered for this study. Two main factors is considered such as design and urban where taken into account in order to select the appropriate and specific passive cooling strategy. The results show that the passive cooling strategy of courtyard would be appropriate for arid regions, however a high thermal mass would be suitable for construction. In conclusion, this work made it possible to choose a suitable passive cooling strategy for all types of construction in hot and dry climates. Finally, this paper puts forward a set of recommendations to improve the passive design of future buildings in hot and arid climates.